2020
DOI: 10.3390/bioengineering7040153
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Functionalization of Biocompatible Scaffolds for Biomedical Applications: A Perspective

Abstract: The burst of research papers focused on the tissue engineering and regeneration recorded in the last years is justified by the increased skills in the synthesis of nanostructures able to confer peculiar biological and mechanical features to the matrix where they are dispersed. Inorganic, organic and hybrid nanostructures are proposed in the literature depending on the characteristic that has to be tuned and on the effect that has to be induced. In the field of the inorganic nanoparticles used for decorating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 198 publications
(230 reference statements)
0
7
0
Order By: Relevance
“…Moreover, following the activation of SPIONs with an oscillating external magnetic field, the differentiation of osteoprogenitor cell populations towards an osteogenic lineage can be favoured [21,27]. In this regard, SPIONs have also demonstrated great potential in the design of magnetic scaffolds for different tissue engineering applications [28,29], especially in the regeneration of bone tissue [30,31], where improved implant integration and newly developed tissue with higher density have been achieved by applying an external magnetic field [32].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, following the activation of SPIONs with an oscillating external magnetic field, the differentiation of osteoprogenitor cell populations towards an osteogenic lineage can be favoured [21,27]. In this regard, SPIONs have also demonstrated great potential in the design of magnetic scaffolds for different tissue engineering applications [28,29], especially in the regeneration of bone tissue [30,31], where improved implant integration and newly developed tissue with higher density have been achieved by applying an external magnetic field [32].…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin is denatured collagen; it has a structure and chemical composition that resembles the extracellular matrix. The studies have shown that HA and Fe 3 O 4 can enhance the mineralization of the scaffold and have a vital role in the proliferation and differentiation of osteoblasts [ 31 ]. Although HA and Fe 3 O 4 have been used as doping elements in scaffolds for Bone TE, the simultaneous incorporation of them in the PCEC/Gel system has not been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…It is not only the first choice for imaging the brain and central nervous system, but also the main tool for evaluating the function of heart disease and detecting tumors [ 125 , 126 , 127 ]. Paramagnetic nanoparticles have the advantages of small size, large specific surface area, good suspension stability, and directional transport and enrichment under the effect of an external magnetic field, which shows great potential applications in the biomedical field [ 128 ]. Among many magnetic nanoparticles, Fe 3 O 4 nanoparticles are magnetic materials with strong magnetism, simple preparation, and good biocompatibility, which are widely used in tumor diagnosis and treatment, immune detection, and gene delivery [ 129 , 130 ].…”
Section: Liposome Nanoparticlesmentioning
confidence: 99%